Analisis Konten Film “Mak Cepluk” Sebagai Pelestarian Permainan Tradisional Indonesia - Safitri, Tsania Firda Ayu; Kurniawan, Fajar Adhi (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2023)
Children's interest in using modern games is very strong, making children less interested in traditional games. The way that can be done to preserve traditional games is to socialize traditional games. One of the effective socialization today is to disseminate it using communication media, namely films. The method used in this research is to use qualitative research methods. The results showed that the content of the movie